Survival relative to pacemaker status after transcatheter aortic valve implantation. Issue 3 (27th January 2021) - Myat, Aung; Mouy, Florence; Buckner, Luke; Cockburn, James; Baumbach, Andreas; MacCarthy, Philip; Banning, Adrian P.; Curzen, Nick; Hilling‐Smith, Roland; Blackman, Daniel J.; Mullen, Michael; de Belder, Mark; et al.
Abstract: Objectives: To determine whether a permanent pacemaker (PPM) in situ can enhance survival after transcatheter aortic valve implantation (TAVI), in a predominantly inoperable or high risk cohort. Background: New conduction disturbances are the most frequent complication of TAVI, often necessitating PPM implantation before hospital discharge. Methods: We performed an observational cohort analysis of the UK TAVI registry (2007–2015). Primary and secondary endpoints were 30‐day post‐discharge all‐cause mortality and long‐term survival, respectively. Results: Of 8, 651 procedures, 6, 815 complete datasets were analyzed. A PPM at hospital discharge, irrespective of when implantation occurred (PPM 1.68% [22/1309] vs. no PPM 1.47% [81/5506], odds ratio [OR] 1.14, 95% confidence interval [CI] 0.71–1.84; p  = .58), or a PPM implanted peri‐ or post‐TAVI only (PPM 1.44% [11/763] vs. no PPM 1.47% [81/5506], OR 0.98 [0.51–1.85]; p  = .95) did not significantly reduce the primary endpoint. Patients with a PPM at discharge were older, male, had right bundle branch block at baseline, were more likely to have received a first‐generation self‐expandable prosthesis and had experienced more peri‐ and post‐procedural complications including bailout valve‐in‐valve rescue, bleeding and acute kidney injury. A Cox proportional hazards model demonstrated significantly reduced long‐term survival in all those with a PPM, irrespective of implantation timing (hazard ratio [HR] 1.14 [1.02–1.26]; p  = .019) and those receiving a PPM only at the time of TAVI (HR 1.15 [1.02–1.31]; p  = .032). The reasons underlying this observation warrant further investigation. Conclusions: A PPM did not confer a survival advantage in the first 30 days after hospital discharge following TAVI.